The Paris Framework for Climate Change capacity building - Khāna, Mijānura Rahamāna 1967-2021; Roberts, J. Timmons; Huq, Saleemul; Hoffmeister, Victoria (Routledge advances in climate change research, 2018)
The Paris Framework for Climate Change Capacity Building aims to fill a gap in the literature by unearthing the ineffective and unsustainable practices of capacity building by bilateral and multilateral agencies in developing countries in the last decade, the gaps and lacunae in those processes, and the way forward. ...